Evaluating potential live-renal donors: Causes for rejection, deferral and planned procedure type, a single-centre experience - Perlis, Nathan; Connelly, Maureen; D’A Honey, John R.; Pace, Kenneth T.; Stewart, Robert (Canadian Urological Association Journal, 2013)
Background: Renal transplantation is the preferred therapy to extend life expectancy and quality of life for patients with chronic kidney disease. There are many barriers in the process of live kidney donation that prevent the timely progression from organ requirement to transplantation, including the progression of the live donor through a medical evaluation. We assess how easily patients complete the donor workup, how often the medical evaluation identifies significant incidental findings, and which surgical procedure is planned for organ retrieval. Methods: We reviewed our donor database and the minutes from our multidisciplinary rounds from 2002 to 2008 to assess how medical, radiological and psychological findings were used to decide on the candidacy of potential donors. Results: Half (50.2%) of patients did not pass the initial health screen. Of the 467 patients who progressed beyond the health screen to the computed tomographic angiogram evaluation, 48 (10.3%) were excluded as donors and 419 (89.7%) were accepted. Of those accepted, 136 (32.5%) were conditional on further medical workup. Of the patients accepted (n=419), 375 (89.5%) were planned for laparoscopic left-sided approach. Conclusions: The vast majority of patients who passed the initial health screen for kidney donation will be accepted as donors, but about one-third will require further workup. It is rare to identify life-threatening disease on screening computerized tomographic angiograph for kidney donor workup.